Nova diet quality scores and risk of weight gain in the NutriNet-Brasil cohort study - Francine Silva dos Santos; Eurídice Martinez Steele; Caroline dos Santos Costa; Kamila Tiemman Gabe; Maria Alvim Leite; Rafael Moreira Claro; Mathilde Touvier; Bernard Srour; Maria Laura da Costa Louzada; Renata Bertazzi Levy; Carlos Augusto Monteiro (Cambridge University Press, 2023)
Abstract Objective: To assess the prospective association of two diet quality scores based on the Nova food classification with BMI gain. Design: The NutriNet-Brasil cohort is an ongoing web-based prospective study with continuous recruitment of participants aged ≥ 18 years since January 2020. A short 24-h dietary recall screener including 'yes/no' questions about the consumption of whole plant foods (WPF) and ultra-processed foods (UPF) was completed by participants at baseline. The Nova-WPF and the Nova-UPF scores were computed by adding up positive responses regarding the consumption of thirty-three varieties of WPF and twenty-three varieties of UPF, respectively. Participants reported their height at baseline and their weight at both baseline and after approximately 15 months of follow-up. A 15-month BMI (kg/m2) increase of ≥5 % was coded as BMI gain. Setting: Brazil. Participants: 9551 participants from the NutriNet-Brasil cohort. Results: Increasing quintiles of the Nova-UPF score were linearly associated with higher risk of BMI gain (relative risk Q5/Q1 = 1·34; 95 % CI 1·15, 1·56), whereas increasing quintiles of the Nova-WPF score were linearly associated with lower risk (relative risk Q5/Q1 = 0·80; 95 % CI 0·69, 0·94). We identified a moderate inverse correlation between the two scores (-0·33) and a partial mediating effect of the alternative score: 15 % for the total effect of the Nova-UPF score and 25 % for the total effect of the Nova-WPF score. Conclusions: The Nova-UPF and Nova-WPF scores are independently associated with mid-term BMI gain further justifying their use in diet quality monitoring systems.